Detecção e quantificação de corantes de importância ambiental empregando sensores químicos baseados em fibras ópticas e polímeros molecularmente impressos - Foguel, Marcos Vinicius [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
Industrial effluents containing dyes are daily released to the environment. The launch of textile effluents causes a considerable environmental degradation, changing the natural color and harming the aquatic biological system. Among these dyes, the class of triphenylmethane dyes is widely used in the textile industry and it presents problems to public health and the environment when discharged in the effluent due to the high toxicity and difficult degradation. An alternative for the detection and quantification of these compounds is the development of biomimetic sensors with optical transduction, employing Molecularly Imprinted Polymers (MIP) as recognition system. The advantage of this methodology is the good selectivity, sensitivity and stability of the MIP and low cost of materials. This work explores different synthesis of MIP for the textile dyes: Basic Red 9 (BR9), Acid Green 16 (AG16) and Methyl Green (MG). For this, the syntheses were evaluated with different functional monomers and molar ratios among the reagents employed for the polymerization. All MIP showed better performance in the ratio 1:3:200 of template, functional monomer and structural monomer, respectively. The dye BR9 showed good interaction with the functional monomer 2-acrylamido-2-methyl-1-propanesulfonic acid by hydrogen bonding, while the dyes MG and AG16 have affinity with the monomer 1-vinylimidazole, by electrostatic and π-cation interaction, respectively. MIP for dyes BR9 and AG16 have good percentage of rebinding (70 and 86%, respectively), satisfactory imprinting factor (1.82 e 6.91, respectively), high selectivity in comparison with other textile dyes and high efficiency in extraction of the respective dyes in sample of textile industrial effluent, presenting recoveries around of 100%. However, the MIP for the dye MG has not presented satisfactory results, with rebinding values below 20%. Probably the MIP performance...

Efluentes industriais contendo corantes são diariamente liberados no meio ambiente. O lançamento de efluentes têxteis provoca uma degradação ambiental considerável, modificando a coloração natural e prejudicando o sistema biológico aquático. Dentre esses corantes, a classe de corantes trifenilmetano é largamente empregada na indústria têxtil e apresenta problemas à saúde pública e ao meio ambiente quando despejados nos efluentes, devido à alta toxicidade e difícil degradação. Uma alternativa para a detecção e quantificação destes compostos é o desenvolvimento de sensores biomiméticos com transdução óptica, empregando como sistema de reconhecimento polímeros molecularmente impressos (MIP). A vantagem desta metodologia é a boa seletividade, sensibilidade, estabilidade dos MIP e baixo custo dos materiais empregados. O presente trabalho explora diferentes sínteses de polímeros impressos para os corantes têxteis: Vermelho Básico 9 (BR9), Verde Ácido 16 (AG16) e Verde de Metila (MG). Para isso foram avaliadas sínteses com diferentes monômeros funcionais e proporções molares entre os reagentes empregados para a polimerização. Todos os MIP apresentaram melhor desempenho na proporção 1:3:200 de molécula molde, monômero funcional e monômero estrutural, respectivamente. O corante BR9 mostrou boa interação com o monômero funcional ácido 2-acrilamino-2-metilpropano sulfônico por meio de ligação de hidrogênio, enquanto que os corantes AG16 e MG apresentaram afinidade com o monômero 1-vinilimidazol, por meio de interação íon-dipolo e π-cátion, respectivamente. Os MIP para os corantes BR9 e AG16 apresentaram boa porcentagem de religação (70 e 86%, respectivamente), fatores de impressão bastante satisfatórios (1,82 e 6,91, respectivamente) alta seletividade frente a outros corantes têxteis e grande eficiência na extração dos respectivos corantes em amostra...
Keywords: Impressão molecular; Fibras oticas; Corantes; Biomimetismo; Monitoramento ambiental; Dyes